Nonlinear optical spin hall effect and long-range spin transport in polariton lasers - Liew, Timothy Chi Hin (2013)
We report on the experimental observation of the nonlinear analogue of the optical spin Hall effect under highly nonresonant circularly polarized excitation of an exciton-polariton condensate in a GaAs/AlGaAs microcavity. The circularly polarized polariton condensates propagate over macroscopic distances, while the collective condensate spins coherently precess around an effective magnetic field in the sample plane performing up to four complete revolutions.